MVC: an integrated mitochondrial variant caller for forensics. (29th July 2019) - Roth, C.; Parson, W.; Strobl, C.; Lagacé, R.; Short, M.
ABSTRACT: Mitochondrial DNA (mtDNA) sequencing is a valuable forensics tool in determining the source of DNA obtained from degraded, damaged or small biological samples. However, despite the recent advances in Massively Parallel Sequencing (MPS), the analysis of mtDNA has remained challenging: alignments can be misleading and may result in incorrect variant calls, and contamination from nuclear DNA from small samples may obscure true variants. In this article, we discuss an integrated approach to solving these issues in a new mito variant caller that integrates various sources of knowledge about mtDNA, including phylotree, EMPOP and NUMTs statistics, and that avoids many of the pitfalls of standard algorithms. The knowledge is integrated into the alignment algorithm itself to distinguish true variant calls from NUMT contamination and sequencing artefacts.